The EFFECTIVENESS OF QUESTIONING STRATEGY FOR TEACHING READING - Diva Luthfiah Mukhlisyah; Maskhurin Fajarin (E-Link Journal, 2024)
The primary objective of this study was to ascertain whether this strategy significantly improved students' reading comprehension skills. Design Research design for class VIII students of SMP Bayt Tamyiz Tukdana-Indramayu for the 2024/2025 academic year. The study population consists of classes VIII of SMP Bayt Tamyiz, totaling 25 students in one class and this research will only be carried out in one class. To obtain research data, the researcher used a test was used as an instrument, incorporating both a pre-test and a post-test, each consisting of 10 multiple-choice questions. The learning process was carried out in three meetings, resulting in a post-test average the researcher conducted a paired sample T-test to analyze the data, revealing The mean post-test score was 79.83, while the mean pre-test score was 50.86. Given a significance score of 0.000 (less than 0.005), the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. Therefore, there is a significant influence of the use of the Questioning Strategy Method on reading. Questioning strategies not only improve understanding but also increase students' ability to make conclusions from the text. In conclusion, questioning strategies proved to be an effective method for teaching reading, promoting better understanding and engagement among middle school students.